Strategije komuniciranja s chatGPT pri kvalitativni analizi besedil - Mesec, Blaž (Socialno delo, 2024)
The article describes experiments in which Human Intelligence (HI) or a human researcher (HR) communicated with Artificial Intelligence (AI/UI), specifically the chatGPT programme, in analysing the text of two interviews in the field of social gerontology. The general framework of the analysis is grounded in Glaser and Strauss's theory, involving steps that range from transcribing the interviews to coding and defining relevant concepts, leading to a tentative theory. The interaction with AI followed the comparative sequence method, which means that both intelligences, HI and UI, researcher and computer programme, alternated in each sequence of analysis. The researcher prompted responses from the programme with input stimuli, evaluated them, conveyed feedback to the UI, and used it as a basis for the next sequence. It was found that the programme is a valuable tool for qualitative analysis as it provides hints and ideas to the researcher, but the guiding and directing role of the researcher (HR) is essential, especially in formulating the final tentative theory. The feedback provided by the researcher in theory formulation contributes to the programme's learning, making it a progressively better assistant over time when used in qualitative text analysis.
Keywords: artificial intelligence; človeška inteligenca; grounded theory; human intelligence; kvalitativna analiza; methodology; metodologija; retirement; umetna inteligenca; upokojitev; utemeljena teorija